2017
DOI: 10.15611/pn.2017.494.05
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Habitat Spectrum of Vascular Flora of Post-Mining “Ruda” Heap in Zabrze-Biskupice

Abstract: Streszczenie: W pracy przedstawiono charakterystykę ekologiczno-siedliskową flory naczyniowej zwałowiska "Ruda" w Zabrzu-Biskupicach. Flora hałdy liczy 164 taksony roślin z 38 rodzin i reprezentuje stadium pośrednie pomiędzy inicjalnym a przejściowym etapem spontanicznej sukcesji roślinności. Dominują w niej rodzime (73,8%), jedno-(20,1%) i wieloletnie (50,6%) gatunki ruderalne (40,2%) i łąkowe (17,7%), o znacznych zdolnościach konkurencyjnych (48,2%), rozsiewane na drodze anemo-(75,6%), zoo-(15,2%) i autochor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Large (380 m 2 ) and medium-sized (130 m 2 ) pioneer communities of therophytes (Conyza canadensis, Trifolium arvense), which produce a large number of seeds and begin to flower relatively early during the vegetative season have developed in sunny places on the dry and acidic substrate. Aggregations of Solidago gigantea, which produce strong underground stolons and are characterized by a wide range of ecological tolerance, are also found here occupying a large area (220 m 2 ) [6,23]. Rostański [1], Woźniak [2], and Banaszek et al [20] also found such aggregations of S. gigantea on other coal mine heaps in the Upper Silesia Industrial Region (southwestern Poland).…”
Section: Zones Of Thermal Activitysupporting
confidence: 60%
See 1 more Smart Citation
“…Large (380 m 2 ) and medium-sized (130 m 2 ) pioneer communities of therophytes (Conyza canadensis, Trifolium arvense), which produce a large number of seeds and begin to flower relatively early during the vegetative season have developed in sunny places on the dry and acidic substrate. Aggregations of Solidago gigantea, which produce strong underground stolons and are characterized by a wide range of ecological tolerance, are also found here occupying a large area (220 m 2 ) [6,23]. Rostański [1], Woźniak [2], and Banaszek et al [20] also found such aggregations of S. gigantea on other coal mine heaps in the Upper Silesia Industrial Region (southwestern Poland).…”
Section: Zones Of Thermal Activitysupporting
confidence: 60%
“…They involved the removal of vegetation and the selection of incoming material. The reclaimed area was then covered with loamy and sandy soils [6].…”
Section: Site Descriptionmentioning
confidence: 99%